Youth Conceptions of Happiness: A Phenomenological Inquiry into Emotional Well-Being - Camilo Ríos, Juan; Abalorio, Bridget (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to explore and describe how Colombian adolescents conceptualize and experience happiness within their sociocultural context. Methods and Materials: This qualitative study employed a phenomenological design to capture the lived experiences of youth. A total of 24 participants (13 females, 11 males), aged 18–25 years, were recruited from various urban and rural regions in Colombia through purposive sampling. Data were collected via semi-structured, in-depth interviews conducted in Spanish, focusing on definitions, sources, and experiences of happiness. Interviews lasted between 45 and 70 minutes and were transcribed verbatim. Data collection continued until theoretical saturation was achieved. Transcripts were analyzed thematically using NVivo 14 software, following an iterative process of coding, clustering, and interpretation to extract the essence of adolescents’ conceptions of happiness. Findings: The analysis generated four overarching themes: (1) Personal Dimensions of Happiness (self-acceptance, autonomy, health, emotional balance, optimism, and achievement); (2) Relational and Social Connections (family support, friendships, romantic relationships, belonging, and community ties); (3) Cultural and Contextual Influences (Colombian identity, spirituality, socioeconomic conditions, education, political climate, and digital culture); and (4) Experiential and Lifestyle Factors (leisure, creativity, nature, mindfulness, kindness, novelty, and balance). Participants consistently emphasized the interdependence of personal strengths, social bonds, cultural traditions, and lifestyle practices in shaping their happiness. Conclusion: This study highlights the multidimensional nature of adolescent happiness, revealing it as a construct deeply embedded in personal growth, relationships, cultural identity, and contextual realities. The findings underscore the importance of adopting culturally sensitive and holistic approaches to promoting youth well-being in Colombia and similar settings. By centering adolescents’ own voices, this research contributes to global understandings of happiness and provides insights for policies, educational initiatives, and community interventions aimed at fostering emotional well-being among youth.